The Effectiveness Test of Application Anthocyanin’s Extract in Fruit Jam From Several Biological - Saati, Elfi Anis; Heidir, Hilwa; Wachid, Moch.; Winarsih, Sri; Haris, Abd.; Nurhakim, Nurhakim (Indonesian Journal of Natural Pigments, 2019)
The study is to investigate the effectiveness of several anthocyanins on quality of papaya jam. It was conducted using a randomized block design, arranged with two factors. The first factor is the anthocyanin with different source with several levels that of control (without pigment), canna flower, grape and skins dragon fruit, factor II is sugar content which is 40%, 50%, and 60%. The results of the study, indicating that there is significant to increase quality products. The best treatment is papaya jam with canna flower anthocyanin pigment and 60% sugar.